CONSTRUCTING A SCALE OF THE BIG FIVE PERSONALITY FACTORS IN THE SPORTS FIELD - Dr. Haidar Abdulwahid Ghadhban (Proximus Journal Publishing, 2025)
This research aims to build a scientific scale to measure the Big Five personality factors in the sports field, which include: openness to experience, agreeableness, neuroticism, extroversion, and conscientiousness. These factors directly affect athletes’ performance and behavior inside and outside sports teams. The research relies on scientific and psychological foundations to design the scale to ensure its accuracy and reliability, which helps coaches and researchers understand individual differences among athletes and analyze their relationship to sports performance
Keywords: personality; factors; analyze